Stress dependent capillary dominated flow in matrix around hydraulic fractures in shale reservoirs and its impact on well deliverability - Moghaddam, R.N. (Society of Petroleum Engineers, 2017)
Understanding the mechanisms of fluid flow in unconventional shale reservoirs is of great interest as these mechanisms have significant impacts on long term economic development of such reservoirs. In shale rocks, the average size of pore/throat is much smaller than the average pore size in conventional rocks which results in higher capillary pressures. Such high capillary pressures can strongly influence the two-phase flow specifically around the wellbore by preventing the fluid flow from matrix to hydraulic fractures and resulting in liquid holdup. In addition, the pronounced poroelastic properties of shale matrix make the flow properties to be extremely sensitive to the effective stress. As a result, the production rate and well deliverability of shale reservoirs can be severely affected by stress dependent capillary pressure around the wellbore area while this impact has not been investigated yet. In this study, a numerical approach was adapted to solve the analytical formulation of two-phase flow considering the capillary and viscous forces in matrix around hydraulic fractures. To evaluate the integrity of the simulation results, the predicted liquid saturation profiles were compared with some experimental data reported in the literature where liquid saturation profiles were measured by CT scanner under both viscous and capillary dominated flow conditions. Then, the two phase flow in tight formations were simulated and the obtained liquid saturation profiles were used to estimate the equivalent relative permeability curves at different stress conditions. The results showed that the liquid holdup in the matrix around the hydraulic fractures can be accumulated even up to a meter that significantly reduces the relative permeability values in this zone. This liquid holdup (or capillary end effects) depends on several parameters including effective stress applied to the formations. In addition, the effects of viscous forces on liquid holdup were investigated in terms of fluid velocity. It is found that, a higher fluid velocity(or flow rate) which can be achieved by increasing drawdown pressure (reduction of bottom hole pressure) can cause a significant damage to the matrix permeability around the hydraulic fractures. This damage also adversely affects flow and can promote the capillary dominated flow. The results of this study improve our understanding of flow mechanisms in unconventional reservoir rocks. This knowledge is required for shale reservoir simulation and cost effective production from hydraulic fractured wells in shale reservoirs.